Evaluasi Atas Sistem Review Pengendalian Intern Dalam Meningkatkan Efektifitas Penjualan Kredit : Studi Kasus PT. Mersifarma Tirmaku Mercusana - Hasibuan, David H.M. (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2004)
The realization of review on internal control of audit seling system and procedure at PT Mersifarma has not used COSO version yet. The firm only used list of internal control in simple review form, namely Internal Control Qustionnaries in order that internal control of credit selling could be carried out effectively and efficiently. By virtue of observation conducted during these several years, operational activity was able to gain efficiency and effectiveness in accordance with the policy of the firmâs management. Keywords : Internal Control; Credit